Toxic effects of tamoxifen on the growth and respiratory activity of Bacillus stearothermophilus - Luxo, C. (2001)
The anticancer drug tamoxifen (TAM) is used as first line therapy in breast cancer. Although tamoxifen is usually considered an estrogen antagonist, several studies suggest alternative mechanisms of action. Bacillus stearothermophilus has been used as a model to clarify the antiproliferative action of tamoxifen putatively related with drug-membrane interaction. According to previous data, TAM induces perturbation of membrane structure along with impairment of bacterial growth. The aim of this work was to correlate the effects of TAM on growth of intact B. stearothermophilus with the respiratory activity of isolated protoplasts of this bacteria. TAM inhibits bacterial growth and oxygen consumption of protoplasts as a function of concentration. Effects on oxygen consumption depend on the substrate used: NADH, allowing to study the full respiratory chain and ascorbate-TMPD to probe the final oxidase segment. The interaction of TAM with the respiratory components occurs at a level preceding the cytochrome oxidase segment.